Asphalt emulsion composition and manufacturing method thereof
By using chloroprene latex copolymerized with sulfur in the asphalt emulsion composition, the problem of insufficient grasp of the asphalt emulsion aggregate in the prior art is solved, and higher paving stability and aggregate adhesion are achieved.
Patent Information
- Application Number
- CN202380056078.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-11
AI Technical Summary
The asphalt emulsion used in the existing gravel sealing process has insufficient aggregate graspability and is difficult to meet the needs of higher pavement stability.
By using chloroprene latex copolymerized with sulfur in the asphalt emulsion composition, a layered structure with excellent aggregate graspability is formed.
The aggregate graspability of the asphalt emulsion composition when making a layered structure is significantly improved, and the adhesion and stability of the paved aggregate are enhanced.
Smart Images

Figure BDA0005255901110000091
Abstract
Description
Technical Field
[0001] The present invention relates to an asphalt emulsion composition and a method for producing the same. Background Art
[0002] Roads paved with asphalt materials are exposed to sunlight, wind and rain, etc. during use, which causes hardening and deterioration, resulting in fine cracks. If rainwater penetrates through these cracks, water penetrates between the asphalt pavement and the roadbed below, causing the asphalt pavement to peel off from there. In addition, during the use of the asphalt pavement, aggregates (such as crushed stones) contained in the pavement fall off, resulting in a rough pavement state.
[0003] As a process for repairing such damaged asphalt pavement, for example, a chip seal process is known. The chip seal process is a process in which an asphalt emulsion is spread on an existing asphalt pavement, and then aggregate is spread and rolled. It should be noted that rolling means applying force to sand, asphalt, etc. to squeeze out air, so that the contact between particles becomes denser and the density is increased.
[0004] In order to impart aggregate-grasping power (hereinafter also referred to as “aggregate-grasping property”) to the asphalt emulsion used in the chip seal process, a polymer having rubber elasticity is generally added as a modifier.
[0005] For example, Patent Document 1 discloses, as a modifier, a styrene / butadiene / styrene (SBS) block copolymer, SBR (styrene butadiene rubber), chloroprene latex, and natural rubber.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: U.S. Patent No. 5,180,428 Summary of the invention
[0009] Problems to be solved by the invention
[0010] Conventionally, asphalt emulsions used in chip seal applications have been modified with polymers having rubber elasticity, such as chloroprene latex.
[0011] However, the aggregate controllability of asphalt emulsions to which these modifiers are added is still insufficient, and further improvement of the aggregate controllability is desired.
[0012] An object of one embodiment of the present invention is to provide an asphalt emulsion composition having excellent aggregate controllability when formed into a layered structure, and a method for producing the same.
[0013] Means for solving problems
[0014] The inventors have conducted studies and found that the use of sulfur-copolymerized chloroprene latex in an asphalt emulsion composition significantly improves the controllability of aggregates when forming a layered structure, compared with the case where a conventional chloroprene latex is used in an asphalt emulsion composition.
[0015] Means for solving the above-mentioned problems include the following.
[0016] <1> An asphalt emulsion composition comprises sulfur-copolymerized chloroprene, asphalt and water.
[0017] <2> according to <1> The asphalt emulsion composition further comprises a surfactant.
[0018] <3> according to <1> or <2> The asphalt emulsion composition, the sulfur copolymerized chloroprene is in the form of particles.
[0019] <4> according to <1> ~ <3> In the asphalt emulsion composition described above, the asphalt is asphalt particles.
[0020] <5> A method for producing an asphalt emulsion composition comprises the step of mixing sulfur-copolymerized chloroprene latex with asphalt.
[0021] <6> according to <5> The method for producing the asphalt emulsion composition, wherein the asphalt is asphalt emulsion.
[0022] <7> according to <5> The method for producing the asphalt emulsion composition, wherein the asphalt is asphalt particles.
[0023] <8> according to <5> ~ <7> The method for producing an asphalt emulsion composition described in any one of the preceding claims comprises the step of polymerizing the chloroprene monomer in the presence of water and 0.01 to 5.0 parts by mass of sulfur relative to 100 parts by mass of the chloroprene monomer to obtain the sulfur-copolymerized chloroprene latex.
[0024] <9> according to <5> ~ <8> In the method for producing an asphalt emulsion composition as described in any one of the preceding claims, the gel content of the sulfur-copolymerized chloroprene latex is 0 to 90% by mass.
[0025] <10> according to <5> ~ <9> In the method for producing an asphalt emulsion composition described above, the solid content of the sulfur-copolymerized chloroprene latex is 0.5 to 20 parts by mass based on 100 parts by mass of the solid content of the asphalt.
[0026] <11> A layered structure comprising <5> ~ <10> An asphalt emulsion composition obtained by any one of the production methods described above.
[0027] <12> An asphalt emulsion composition is made by <5> ~ <10> It is obtained by any of the manufacturing methods described above.
[0028] <13> according to <12> The asphalt emulsion composition forms an island structure after drying.
[0029] <14> according to <12> or <13> The asphalt emulsion composition has a gel content of 0 to 90% by mass of sulfur copolymerized chloroprene latex.
[0030] <15> according to <12> ~ <14> In the asphalt emulsion composition described above, the solid content of the sulfur-copolymerized chloroprene latex is 0.5 to 20 parts by mass based on 100 parts by mass of the solid content of the asphalt emulsion.
[0031] <16> A latex composition for asphalt modification comprises sulfur-copolymerized chloroprene latex and water.
[0032] Effects of the Invention
[0033] According to one embodiment of the present invention, there is provided an asphalt emulsion composition having excellent aggregate controllability when formed into a layered structure, and a method for producing the same. DETAILED DESCRIPTION
[0034] Hereinafter, the contents of the present invention will be described in detail. The contents of the constituent elements described below may be described based on representative embodiments of the present invention, but the present invention is not limited to such embodiments.
[0035] In the present specification, "to" indicating a numerical range is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0036] In the present specification, "to" indicating a numerical range means that the units described before and after it represent the same unit unless otherwise specified.
[0037] In the present specification, a combination of two or more preferred aspects is a more preferred aspect.
[0038] In this specification, the total solid content refers to the total mass of the components obtained by excluding the solvent or the dispersion medium from all the components of the composition.
[0039] Hereinafter, the present invention will be described in detail.
[0040] (Asphalt emulsion composition)
[0041] The asphalt emulsion composition of the present invention comprises sulfur-copolymerized chloroprene, asphalt and water.
[0042] Since the asphalt emulsion composition has the above-mentioned structure, it is excellent in aggregate controllability when it is made into a layered structure. The reason for this is not clear, but it is presumed as follows.
[0043] The tensile strength of the dried film obtained by drying the sulfur-copolymerized chloroprene latex is superior to that of the dried film obtained by the non-sulfur-copolymerized chloroprene latex. It is presumed that this is because the copolymerized sulfur serves as a crosslinking point, crosslinking between polymer chains occurs during the drying process, and the film strength is improved.
[0044] As described above, the asphalt emulsion composition according to the present invention contains the asphalt emulsion and the sulfur-copolymerized chloroprene latex. Therefore, when the composition is dried, it is considered that a sea-island structure with chloroprene as the sea portion is obtained.
[0045] It is inferred that the sulfur-copolymerized chloroprene as the sea portion is integrated by crosslinking and thus easily forms a mesh-like network having rubber elasticity throughout the entire dry residue, thereby imparting rubber elasticity when the layered structure is formed, thereby improving the controllability of the aggregate.
[0046] The sulfur-copolymerized chloroprene latex will be described in detail below.
[0047] <Sulfur copolymerized chloroprene>
[0048] The sulfur-copolymerized chloroprene may be obtained by copolymerizing a 2-chloro-1,3-butadiene monomer (hereinafter also referred to as a "chloroprene monomer") and sulfur, or may be obtained by copolymerizing a chloroprene monomer or a monomer copolymerizable with chloroprene and sulfur.
[0049] The monomer copolymerizable with chloroprene is not particularly limited unless the purpose of the present invention is impaired, and examples thereof include 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, acrylic acid and its esters, and methacrylic acid and its esters. Among them, the monomer copolymerizable with chloroprene is preferably 2,3-dichloro-1,3-butadiene and 1-chloro-1,3-butadiene, and more preferably 2,3-dichloro-1,3-butadiene.
[0050] The content of the monomer copolymerizable with chloroprene is preferably in the range of 0 to 20 parts by mass relative to 100 parts by mass of 2-chloro-1,3-butadiene (chloroprene).
[0051] The monomer copolymerizable with chloroprene may be one kind alone or two or more kinds may be used in combination. By making the content of the monomer copolymerizable with chloroprene 20 parts by mass or less relative to 100 parts by mass of 2-chloro-1,3-butadiene (chloroprene), good tensile strength can be maintained.
[0052] The asphalt emulsion composition of the present invention preferably comprises sulfur-copolymerized chloroprene latex and asphalt emulsion, and forms an island-in-sea structure after drying. In the layered structure obtained by drying the asphalt emulsion composition, there are asphalt regions (islands) in the sulfur-copolymerized chloroprene regions (seas), so the aggregate controllability is excellent.
[0053] As the drying conditions for forming the sea-island structure, the drying time is preferably 1 minute to 168 hours, and the drying temperature is preferably 10°C to 95°C. From the viewpoint of making it easier to form the sea-island structure, the drying time is more preferably 30 minutes to 96 hours, and more preferably 18 to 36 hours. From the above viewpoints, the drying temperature is more preferably 20°C to 85°C, more preferably 30 to 75°C, and particularly preferably 50 to 75°C.
[0054] The drying method is not particularly limited, and a known method can be adopted. For example, a drying method using warm air, hot air, or low-humidity air can be mentioned.
[0055] The sulfur-copolymerized chloroprene latex can be obtained by polymerizing chloroprene monomer in the presence of sulfur and water.
[0056] The solid content of the sulfur-copolymerized chloroprene latex is preferably 0.5 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, further preferably 1.0 to 10 parts by mass, and particularly preferably 2.0 to 5.0 parts by mass, based on 100 parts by mass of the solid content of the asphalt emulsion.
[0057] The sulfur-copolymerized chloroprene may be used alone or in combination of two or more.
[0058] The shape of the sulfur-copolymerized chloroprene is not particularly limited, but particles are preferred.
[0059] The shape of the particles is not particularly limited, and may be spherical or elliptical, but is preferably spherical.
[0060] The z-average particle size of the sulfur-copolymerized chloroprene is preferably 50 to 500 nm, more preferably 60 to 400 nm, and even more preferably 80 to 300 nm.
[0061] The z-average particle size can be determined using a dynamic light scattering photometer (ZETASIZER (registered trademark) Nano-S manufactured by Malvern Panalytical Ltd.).
[0062] From the viewpoint of making it easier to form a sea-island structure in which the sulfur-copolymerized chloroprene serves as the sea part, the ratio of the z-average particle size of the sulfur-copolymerized chloroprene to the z-average particle size of the asphalt (z-average particle size of the sulfur-copolymerized chloroprene / z-average particle size of the asphalt) is preferably 0.0025 to 1.00, more preferably 0.006 to 0.250, and even more preferably 0.0125 to 0.050.
[0063] It is considered that when the z-average particle size of sulfur-copolymerized chloroprene / z-average particle size of asphalt is within the above range, the particle size of sulfur-copolymerized chloroprene particles is much smaller than that of asphalt, so that when the asphalt emulsion composition is dried, a sea-island structure with chloroprene as the sea portion is obtained.
[0064] In one embodiment of the present invention, the latex composition for asphalt modification preferably contains sulfur-copolymerized chloroprene latex and water.
[0065] In another embodiment of the present invention, the particles in the sulfur-copolymerized chloroprene latex are used as sulfur-copolymerized chloroprene.
[0066] <<Gel Content>>
[0067] The gel content in the sulfur-copolymerized chloroprene latex is preferably 0 to 90% by mass, more preferably 5 to 85% by mass, and even more preferably 15 to 75% by mass, from the viewpoint of excellent aggregate controllability.
[0068] The gel content can be determined as the content of the sulfur-copolymerized chloroprene rubber latex insoluble in tetrahydrofuran (hereinafter also referred to as "tetrahydrofuran-insoluble content"). The tetrahydrofuran-insoluble content can be determined by the measurement method described in the examples below.
[0069] <Sulfur>
[0070] The sulfur copolymerized with the chloroprene monomer is not particularly limited, but preferably is elemental sulfur that is substantially composed of sulfur atoms and can be used as a crosslinking agent for crosslinking various rubbers. Preferably, it is elemental sulfur that acts on the carbon-carbon double bond portion in the monomer unit of the conjugated diene. The sulfur may be powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, etc. The shape of the sulfur is not particularly limited, and may be cyclic or chain.
[0071] From the viewpoint of better aggregate control when forming a layered structure, the sulfur content in the sulfur-copolymerized chloroprene latex is preferably 0.01 to 5.0 mass %, more preferably 0.05 to 0.6 mass %, and even more preferably 0.1 to 0.5 mass % based on the total mass of the sulfur-copolymerized chloroprene latex.
[0072] [Method for producing sulfur-copolymerized chloroprene latex]
[0073] The method for copolymerizing the chloroprene monomer and sulfur (the method for producing the sulfur-copolymerized chloroprene latex) is not particularly limited, but emulsion polymerization is preferred, and aqueous emulsion polymerization is particularly preferred industrially.
[0074] As the emulsifier for emulsion polymerization, anionic surfactants, nonionic surfactants, and compounds that function as protective colloids such as polyvinyl alcohol are preferred.
[0075] Specific examples of the anionic surfactant include rosin acid soap, sodium salt of naphthalenesulfonic acid condensate, sodium salt of dodecylbenzenesulfonic acid, sodium salt of dodecylsulfuric acid, and the like.
[0076] Specific examples of the nonionic surfactant include polyoxyethylene alkyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and the like.
[0077] When rosin acid soap is used as the emulsifier, the amount of rosin acid soap used is preferably 3 to 8 parts by mass, more preferably 3 to 5 parts by mass, based on rosin acid conversion, per 100 parts by mass of the total of the chloroprene monomer and the monomer copolymerizable with the chloroprene monomer.
[0078] When the amount of rosin acid soap used is 3 parts by mass or more, good emulsification can be achieved, good polymerization heat generation control can be achieved, the formation of agglomerates can be suppressed, and a good product appearance can be achieved. When the amount of rosin acid soap used is 8 parts by mass or less, slow heating during polymerization is easily achieved, which is preferred.
[0079] The sodium salt of the naphthalenesulfonic acid condensate is a condensate of sodium naphthalenesulfonate and formaldehyde. By adding the sodium salt of the naphthalenesulfonic acid condensate, the occurrence of the above-mentioned problem can be suppressed even in a system emulsified with 3 parts by mass or less of rosin acid soap.
[0080] As the initiator for polymerization, a common free radical polymerization initiator can be used. For example, in the case of emulsion polymerization, common organic or inorganic peroxides such as benzoyl peroxide, potassium persulfate, ammonium persulfate, and azo compounds such as azobisisobutyronitrile can be used. A cocatalyst such as anthraquinone sulfonate, potassium sulfite, sodium sulfite, etc. can be used appropriately.
[0081] Generally, in the production of sulfur-copolymerized chloroprene latex, a molecular weight regulator (chain transfer agent) may be used during polymerization for the purpose of obtaining a copolymer having a desired molecular weight and distribution.
[0082] The chain transfer agent is not particularly limited, and examples thereof include alkyl xanthate disulfide represented by O,O-diisopropyl dithiobis(thioformic acid) and alkyl mercaptan represented by dodecyl mercaptan.
[0083] The chain transfer agent may be used alone or in combination of two or more.
[0084] Generally, in the production of sulfur-copolymerized chloroprene latex, a polymerization terminator is added to stop the reaction at a time point when a predetermined polymerization rate is reached in order to obtain a polymer having a desired molecular weight and distribution. The polymerization terminator is not particularly limited, and commonly used terminators such as phenothiazine, p-tert-butylcatechol, hydroquinone, hydroquinone monomethyl ether, and diethylhydroxylamine can be used.
[0085] In the method for producing a sulfur-copolymerized chloroprene latex, the amount of sulfur blended is preferably 0.01 to 5.0 parts by mass, more preferably 0.05 to 0.60 parts by mass, and even more preferably 0.10 to 0.50 parts by mass, relative to 100 parts by mass of 2-chloro-1,3-butadiene (chloroprene) or relative to 100 parts by mass of the total of the chloroprene monomer and the monomer copolymerizable with the chloroprene monomer.
[0086] When the amount of sulfur added is 0.01 parts by mass or more, the crosslinking reactivity of the sulfur-copolymerized chloroprene latex is improved. When sulfur is added in an amount of 5.0 parts by mass or less, the polymerization reaction is not inhibited, and a good polymerization conversion rate can be obtained.
[0087] It should be noted that the sulfur used in the reaction is the sulfur whose entire amount used for blending remains in the sulfur-copolymerized chloroprene rubber latex.
[0088] When chloroprene and a copolymerizable monomer are used, the amount of the copolymerizable monomer blended is preferably in the range of 0 to 20 parts by mass based on 100 parts by mass of 2-chloro-1,3-butadiene (chloroprene).
[0089] The solid content of the sulfur-copolymerized chloroprene latex is preferably 0.5 to 20.0 parts by mass, more preferably 1.0 to 10.0 parts by mass, and even more preferably 2.0 to 5.0 parts by mass, based on 100 parts by mass of the solid content of the asphalt.
[0090] <Asphalt>
[0091] Asphalt is not particularly limited, and known and commonly used asphalt can be used. Examples of asphalt include straight run asphalt, air-blown asphalt, semi-air-blown asphalt, natural asphalt, modified asphalt, solvent deasphalted asphalt, tar, asphaltene such as asphalt, heavy oil A, heavy oil B, and heavy oil C.
[0092] The content of asphalt is preferably 50 to 99.9% by mass, more preferably 83 to 99% by mass, and even more preferably 89 to 99% by mass, relative to 100% by mass of the solid content of the asphalt emulsion composition.
[0093] The content of asphalt is preferably 30 to 74% by mass, more preferably 40 to 72% by mass, and even more preferably 50 to 70% by mass, relative to 100% by mass of the asphalt emulsion composition.
[0094] The asphalt may be used alone or in combination of two or more.
[0095] The asphalt is preferably asphalt particles. The shape of the particles is not particularly limited, and may be spherical or elliptical. Among them, the shape of the asphalt particles is preferably spherical.
[0096] The z-average particle size of the asphalt is preferably 0.5 to 20.0 μm, more preferably 1.0 to 10.0 μm, and even more preferably 2.0 to 8.0 μm.
[0097] The z-average particle size can be determined using a dynamic light scattering photometer (ZETASIZER (registered trademark) Nano-S manufactured by Malvern Panalytical Ltd.).
[0098] <<Surfactants>>
[0099] The asphalt emulsion composition preferably also comprises a surfactant.
[0100] The surfactant is not particularly limited, and examples thereof include anionic surfactants, cationic surfactants, and nonionic surfactants.
[0101] Examples of anionic surfactants include neutralized products of tall oil and sodium hydroxide or potassium hydroxide. Examples of cationic surfactants include alkylamide polyamines, alkyl imidazo polyamines, N-alkyl polypropylene diamines, hydrochlorides and phosphates of other amines. Examples of nonionic surfactants include polyoxyethylene alkyl ethers, sorbitan fatty acid esters, and polyoxyethylene sorbitan fatty acid esters.
[0102] Among these, as the surfactant, a nonionic surfactant is preferred, and a polyoxyethylene alkyl ether is more preferred.
[0103] Examples of the polyoxyethylene alkyl ethers include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene myristyl ether, polyoxyethylene octyldodecyl ether, polyoxyalkylene alkyl ethers, polyoxyphenylene distyrenated phenyl ether, polyoxyethylene tribenzyl phenyl ether, polyoxyalkylene alkenyl ether, and polyoxyethylene nonylphenyl ether.
[0104] The surfactant may be obtained by synthesis or may be a commercially available product.
[0105] Examples of commercially available products include Emarugen 103, 104P, 106, 108, 109P, 120, 123P, 130K, 147, 150, 210P, 220, 306P, 320P, 350, 404, 408, 409PV, 420, 430, 705, 707, 709, 1108, 1118S-7 0. 1135S-70, 1150S-60, 2020G-HA, 2025G, LS-106, LS-110, LS-114, MS-110, A- 60. A-90, B-66, PP-290, Leather PD-420, PD-430, PD-430S, PD450, SP-L10, AS -10V, AO-10V, AO-15V, TW-L120, TW-L106, TW-P120, TW-S120V, TW-S320V, TW-O 120V, TW-O106V, TW-IS399C, TW-L120, 430V, 440V, 460V, MS-50, MS-60, MO -60, MS-165V, Emax 1112, 3199V, 3299V, 3299RV, 4110, CH-25, CH-40, CH-60(K ), Amino 102, 105, 105A, 302, 320, Amino PK-02S, L-02, Amino L-95 (the above are manufactured by Kao Co., Ltd.).
[0106] The content of the surfactant is preferably 0.1 to 10.0 parts by mass, more preferably 0.2 to 7.0 parts by mass, and even more preferably 0.3 to 6.0 parts by mass, based on 100 parts by mass of the solid content of the asphalt emulsion composition.
[0107] The surfactant may be used alone or in combination of two or more.
[0108] <Water>
[0109] The water is not particularly limited, and examples thereof include industrial water and tap water.
[0110] The amount of water is preferably 25 to 400 parts by mass, more preferably 35 to 230 parts by mass, and even more preferably 40 to 150 parts by mass, based on 100 parts by mass of the solid content of the asphalt emulsion composition.
[0111] The asphalt emulsion composition may further contain components other than the above-mentioned sulfur-copolymerized chloroprene latex, asphalt, surfactant, and water (hereinafter also referred to as "other components").
[0112] As other components, for example, salts such as calcium chloride, film-forming agents, thickening stabilizers, and retarder agents are mentioned for stabilizing emulsions.
[0113] Stress creep recovery of asphalt emulsion composition: Although MSCR (multiple stress creep recovery) also depends on the mass percentage of the solid content of sulfur-copolymerized chloroprene latex in the asphalt composition, from the perspective of excellent aggregate control, it is preferably 20 to 95%, more preferably 20 to 80%, further preferably 20 to 60%, and particularly preferably 20 to 40%.
[0114] The MSCR of the asphalt emulsion composition can be determined by the method described in the examples below.
[0115] <Method for producing asphalt emulsion composition>
[0116] The method for producing an asphalt emulsion composition comprises a step of mixing sulfur-copolymerized chloroprene latex with asphalt, and more preferably comprises a step of mixing asphalt emulsion with sulfur-copolymerized chloroprene latex. In the method for producing an asphalt emulsion composition, the asphalt is preferably asphalt particles.
[0117] In addition, the method for producing the asphalt emulsion composition preferably includes the following step: polymerizing the chloroprene monomer in the presence of 0.01 to 5.0 parts by mass of sulfur (more preferably 0.05 to 0.60 parts by mass of sulfur) and water relative to 100 parts by mass of the above-mentioned chloroprene monomer to obtain the above-mentioned sulfur-copolymerized chloroprene latex (hereinafter also referred to as "sulfur-copolymerized chloroprene latex preparation step").
[0118] The method for producing an asphalt emulsion composition preferably includes a step of adding asphalt, a surfactant, and water (hereinafter also referred to as an "asphalt emulsion forming step"). In the asphalt emulsion forming step, the order of adding asphalt, a surfactant, and water is not particularly limited, as long as an asphalt emulsion is formed, and they can be added separately or simultaneously. For example, various surfactants can be added to asphalt and then mixed with water to form an asphalt emulsion.
[0119] Alternatively, the surfactant and water may be added followed by the addition of asphalt.
[0120] The method for mixing the sulfur-copolymerized chloroprene rubber latex with asphalt, surfactant and water is not particularly limited, and various known methods can be cited, for example, a method of mixing using a degassing kneading machine, a dry ball mill, a dry bead mill, a scraper planetary mixer, a container rotation planetary mixer, a grinder, a mortar, a homogenizer, a rubber mill, etc. Among them, as the above-mentioned mixing method, it is desirable to perform emulsification using a homogenizer or a rubber mill.
[0121] The method for producing the asphalt emulsion composition may include a step of adding the above-mentioned other components as necessary. In addition, for example, after the sulfur-copolymerized chloroprene rubber latex preparation step, a step of adjusting the pH may be included.
[0122] The pH of the sulfur-copolymerized chloroprene latex after the pH adjustment step is preferably 1.0 to 4.5, more preferably 1.5 to 3.5.
[0123] The pH adjuster used in the step of adjusting pH is not particularly limited, and a known pH adjuster can be used.
[0124] The asphalt emulsion composition involved in the present invention is preferably an asphalt emulsion composition produced by the above-mentioned method for producing an asphalt emulsion composition, and more preferably, the asphalt emulsion composition produced by the above-mentioned method for producing an asphalt emulsion composition forms an island structure after drying.
[0125] It is estimated that in the composition obtained by the method for producing an asphalt emulsion composition according to the present invention, that is, by mixing the sulfur-copolymerized chloroprene latex with asphalt, a sea-island structure in which chloroprene serves as the sea portion is obtained.
[0126] From the viewpoint of excellent aggregate controllability, the asphalt emulsion composition of the present invention can be suitably used for road paving. As a method for road paving, for example, a chip seal process method can be cited, and a method of sequentially stacking an asphalt emulsion composition and aggregates on the surface side of a road and then rolling them can be cited.
[0127] In the chip seal process, the asphalt emulsion composition layer and the aggregate layer may be formed into a single layer (seal layer) or a multilayer layer (protective coating layer) in which these single layers are stacked.
[0128] From the perspective of excellent aggregate controllability, the above-mentioned asphalt emulsion composition can be used not only in the chip seal process, but also in drag seals, bonding layers, and roadbed binders (including on-road roadbed recycling and in-situ cold recycling).
[0129] Example
[0130] The present invention will be described below with reference to Examples and Comparative Examples, but the present invention is not limited to the following examples.
[0131] <Manufacturing of Asphalt Emulsion>
[0132] Into a container having an internal volume of 5 liters, 3.50 kg of pure water heated to 80°C was placed, and 24 g of dimethyl hardened tallow amine (manufactured by NOF Corporation, product name: Nissan Amin (registered trademark) ABT) as a surfactant, 19 g of 35% by mass hydrochloric acid (manufactured by Kanto Chemical Co., Ltd.), and 14 g of calcium chloride (manufactured by Kanto Chemical Co., Ltd.) were added to prepare a surfactant aqueous solution. The surfactant aqueous solution and 6.50 kg of straight-run asphalt (manufactured by Showa Asphalt Industries, Ltd., product name: SA120-150) heated and melted at 140°C were emulsified using a rubber mill (manufactured by IKA Japan Co., Ltd., product name: Magic LAB (registered trademark) XP) at an asphalt emulsion production rate of 0.5 L / min to obtain an asphalt emulsion having a solid content of 65% by mass and a z-average particle size of 5 μm.
[0133] <Manufacturing of Sulfur Copolymerized Chloroprene Latex>
[0134] A reactor having an internal volume of 3 liters was charged with 1.00 kg (100 parts by mass) of 2-chloro-1,3-butadiene (chloroprene) (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.93 kg of pure water, 34 g of rosin acid (manufactured by Arakawa Chemical Industry Co., Ltd., Rozin HTR), 1.0 g (0.10 parts by mass) of sulfur, 1.5 g of O,O-diisopropyl dithiobis(thioformate) (manufactured by Sanshin Chemical Industry Co., Ltd.), 5.9 g of potassium hydroxide, 4.9 g of sodium hydroxide, and 0.44 mg of copper sulfate, and emulsified to convert rosin acid into rosin soap (a mixture of potassium rosinate and sodium rosinate). Then, using potassium persulfate as an initiator, polymerization was carried out under a nitrogen atmosphere at a polymerization starting temperature of 40° C., and the temperature was raised to 45° C. when the polymerization conversion rate reached 90%, and polymerization was carried out. When the polymerization conversion rate was confirmed to be 95%, the polymerization was stopped. Next, unreacted monomers were removed by steam distillation, and 10 g of diethanolamine (manufactured by Nippon Shokubai Co., Ltd.) and 60 g of a 70% aqueous solution of polyoxyethylene alkyl ether (manufactured by Kao Corporation, product name: Emergen 1118S-70) were added to obtain sulfur-copolymerized chloroprene latex particles having a solid content of 48.0% by mass. The z-average particle size was 128 nm.
[0135] [Example 1]
[0136] <Manufacturing of Asphalt Emulsion Composition>
[0137] To 40 g of the asphalt emulsion prepared above (solid content: 65% by mass) heated to 60°C, 1.63 g of the product obtained by adding 0.5 g of 35% by mass hydrochloric acid (manufactured by Kanto Chemical Co., Ltd.) to the sulfur-copolymerized chloroprene latex synthesized above and adjusting the pH to 2.0 was added to obtain an asphalt emulsion composition.
[0138] It should be noted that the addition amount of the sulfur copolymerized chloroprene rubber latex was determined such that the solid content in the sulfur copolymerized latex was 3 parts by mass when the solid content in the asphalt emulsion was 100 parts by mass. Specifically, the addition amount of the sulfur copolymerized chloroprene rubber latex was calculated based on the following formula.
[0139] Addition amount of sulfur copolymerized chloroprene rubber latex = Amount of asphalt emulsion (40 g) × (Solid content of asphalt emulsion) × (3 parts by mass / 100 parts by mass) ÷ (Solid content of sulfur copolymerized chloroprene rubber latex)
[0140] It should be noted that hydrochloric acid is sometimes used for the purpose of adjusting the pH after the sulfur copolymerized chloroprene rubber latex is prepared. However, hydrochloric acid volatilizes under the conditions for measuring the solid content, so it does not affect the solid content.
[0141] <Gel content of sulfur copolymerized chloroprene rubber latex>
[0142] The gel content of the sulfur copolymerized chloroprene rubber latex was determined as the content of the sulfur copolymerized chloroprene rubber latex insoluble in tetrahydrofuran (THF) (THF-insoluble component). 0.5 g of the sulfur copolymerized chloroprene rubber latex synthesized above (in the above latex, the water content was in the range of 40% to 65% by mass) was dropped into 100 mL of tetrahydrofuran, and after shaking overnight, the THF solution was separated using a centrifuge, and the THF-soluble phase of the supernatant was extracted. The extracted soluble phase was heated to 100 °C, and tetrahydrofuran was evaporated and dried over 1 hour to calculate the mass of the sulfur copolymerized chloroprene rubber latex dissolved in the THF-soluble phase. Then, the mass of the sulfur copolymerized chloroprene rubber latex dissolved in THF was subtracted from the mass of the sulfur copolymerized chloroprene rubber in the sulfur copolymerized chloroprene rubber latex, and further divided by the mass of the sulfur copolymerized chloroprene rubber in the sulfur copolymerized chloroprene rubber latex to calculate the content of the sulfur copolymerized chloroprene rubber latex insoluble in tetrahydrofuran (THF-insoluble component). The results are shown in Table 1.
[0143] <Preparation of sample for MSCR (multiple stress creep recovery) measurement>
[0144] 40 g of the asphalt emulsion containing the sulfur copolymerized chloroprene rubber latex prepared above was poured into a silicone bucket with a bottom area of 216 mm × 175 mm and a depth of 40 mm, covering the entire bucket. Then, after drying at 23 °C for 24 hours and then drying in an oven at 60 °C for 24 hours, a sample for stress creep recovery (MSCR) measurement was obtained.
[0145] <Evaluation of aggregate retention>
[0146] In the evaluation of aggregate controllability, stress creep recovery (MSCR: multiple stress creep recovery) was measured based on the AASHTO (America Association of State Highway and Transportation Officials) T350-14 standard and evaluated as an index of aggregate controllability.
[0147] Specifically, a rheometer (MCR301 manufactured by Anton Paar) was used for the measurement, and a parallel plate specified in JIS K7244-10:2005 and having a diameter of 25 mm was used as a measurement jig.
[0148] The apparatus was set to 64° C. and the temperature was sufficiently adjusted. Then, about 1.0 g of the measurement sample prepared above was set, and the excess sample was removed before measurement.
[0149] The measurement was performed by the following steps.
[0150] (1) Record the deformation (A) before stress is applied.
[0151] (2) Apply a stress of 3.2 kPa for 1 second and record the deformation (B) at this time.
[0152] (3) After stopping the stress application, wait for 9 seconds (during which time the sample will return to its original shape due to rubber elasticity) and record the deformation after 9 seconds (C).
[0153] The above steps (1) to (3) were repeated 10 times.
[0154] In each cycle, the amount of recovery from the deformation due to stress was calculated using the following formula.
[0155] (Deformation (B) - Deformation (C)) ÷ (Deformation (B) - Deformation (A)) × 100
[0156] The above formula was used to calculate in 10 cycles, and the average value was obtained as stress creep recovery. The higher the value of stress creep recovery (MSCR), the better the aggregate controllability can be said to be.
[0157] It should be noted that it can be said that the samples with MSCR exceeding 20% also have sufficient aggregate control in actual paving.
[0158] <Particle size>
[0159] The sulfur-copolymerized chloroprene rubber latex or asphalt emulsion was diluted with pure water to 0.01 to 0.1% by mass, and the resulting solution was measured for z-average particle size using a dynamic light scattering photometer (ZETASIZER (registered trademark) Nano-S manufactured by Malvern Panalytical Ltd.).
[0160] <Polymerization Conversion Rate>
[0161] The emulsion after polymerization was collected and dried at 100° C. for 2 hours to calculate the polymerization conversion rate from the solid content.
[0162] In addition, the solid content and the polymerization conversion rate were calculated|required from the following formula.
[0163] Solid content [mass %] = [(mass after drying at 100°C for 2 hours) / (mass of latex before drying)] × 100
[0164] Polymerization conversion rate [%] = [(polymer production amount / monomer input amount)] × 100
[0165] Here, the amount of polymer generated is obtained by subtracting the solid content other than the polymer from the solid content after polymerization.
[0166] [Examples 2 to 9 and Comparative Examples 1 to 3]
[0167] In Examples 2 to 9 and Comparative Examples 1 to 3, sulfur and O,O-diisopropyl dithiobis(thioformate) were changed to the amounts shown in Table 1, and sulfur-copolymerized chloroprene latexes were prepared in the same manner as in Example 1. Also, asphalt emulsion compositions were prepared in the same manner as in Example 1 using the prepared sulfur-copolymerized chloroprene latexes.
[0168] The obtained asphalt emulsion composition was used to prepare a sample for MSCR measurement, and the aggregate controllability was evaluated. The results are shown in Table 1.
[0169] [Table 1]
[0170]
[0171] The MSCR of the asphalt emulsions of Examples 1 to 9 of the present invention all exceeded 20%, which is higher than that of the asphalt emulsions of Comparative Examples 1 to 3, indicating that the asphalt emulsions have excellent aggregate controllability when formed into a layered structure.
[0172] Industrial Availability
[0173] The asphalt emulsion composition of the present invention can be suitably used in a repair process for deteriorated asphalt pavements, for example, it can be used as an asphalt emulsion as a binder for chip seals, drag seals, fog seals, slurry seals, and roadbed regeneration.
Claims
1. An asphalt emulsion composition comprising sulfur-copolymerized chloroprene, asphalt and water.
2. The asphalt emulsion composition according to claim 1, further comprising a surfactant.
3. The asphalt emulsion composition according to claim 1 or 2, wherein the sulfur-copolymerized chloroprene is in the form of particles.
4. The asphalt emulsion composition according to claim 1 or 2, wherein the asphalt is asphalt particles.
5. A method for producing an asphalt emulsion composition, comprising the step of mixing a sulfur-copolymerized chloroprene latex with asphalt. 6 . The method for producing an asphalt emulsion composition according to claim 5 , wherein the asphalt is an asphalt emulsion. 7 . The method for producing an asphalt emulsion composition according to claim 5 , wherein the asphalt is asphalt particles.
8. The method for producing an asphalt emulsion composition according to claim 5 or 6, comprising the step of polymerizing the chloroprene monomer in the presence of water and 0.01 to 5.0 parts by mass of sulfur relative to 100 parts by mass of the chloroprene monomer to obtain the sulfur-copolymerized chloroprene latex. 9 . The method for producing an asphalt emulsion composition according to claim 5 , wherein the sulfur-copolymerized chloroprene latex has a gel content of 0 to 90% by mass. 10 . The method for producing an asphalt emulsion composition according to claim 5 , wherein the solid content of the sulfur-copolymerized chloroprene latex is 0.5 to 20 parts by mass based on 100 parts by mass of the solid content of the asphalt.
11. A layered structure comprising an asphalt emulsion composition produced by the production method according to claim 5 or 6.
12. An asphalt emulsion composition, which is produced by the production method according to claim 5 or 6.
13. The asphalt emulsion composition according to claim 12, which forms a sea-island structure after drying.
14. The asphalt emulsion composition according to claim 12, wherein the gel content of the sulfur-copolymerized chloroprene latex is 0 to 90% by mass. 15 . The asphalt emulsion composition according to claim 12 , wherein the solid content of the sulfur-copolymerized chloroprene latex is 0.5 to 20 parts by mass based on 100 parts by mass of the solid content of the asphalt emulsion.
16. A latex composition for asphalt modification, comprising sulfur-copolymerized chloroprene latex and water.
Citation Information
Patent Citations
In situ rejuvenation of aged and cracked asphalt pavement
US5180428A